DEVELOPMENT OF NEARPOD BASED INTERACTIVE MULTIMEDIA IN FIFTH GRADE IPAS LEARNING ON THE ECONOMIC CONDITIONS IN MY REGION - Evi Fitria Cahyaningrum (PGMI Fakultas Tarbiyah Universitas Islam Jember, 2025)
In the elementary education curriculum, learning about economic activities is often considered difficult for elementary school students to understand. Therefore, the use of nearpod-based interactive multimedia can increase student engagement with abstract and contextual materials such as economic conditions in their area. The purpose of this study is to develop nearpod-based interactive multimedia in fifth grade elementary school science learning. The researcher used the type of research and development Research and Development (R&D) referring to the Borg and Gall model that has been modified by Sugiyono. The results of this product development obtained a percentage of 96.66% valid category from material experts, 98.18% very valid category from design experts, 91.11% very valid category from language experts, and 93.33% very valid category from education practitioners. Based on the results of the pretest posttest, the N-Gain value was obtained = 0.88. When converted into n-gain interpretation, nearpod-based interactive multimedia is included in the category of having high effectiveness. Student and teacher responses obtained a percentage of 100%, so that the nearpod-based interactive multimedia that has been developed is categorized as very practical.